Los barbones o bethlemitas, la Orden Hospitalaria Americana rescatada del olvido por las Tradiciones de Palma - Adriazola Silva, Juan Carlos (2018)
In the collective memory of the Peruvians of the present, the name of the Hospital Order of the Betlemites is practically forgotten. However, when reading the Peruvian Traditions of Ricardo Palma, the name of that religious institution that remained in Peru for almost three hundred years, resurfaces with new vigor to open the panorama of an interesting time in the history of medicine and the health of our ancestors. Along with this historical vision, comes also the literary part, which is born from the ingenious pen of Palma, when telling us about characters, customs and facts of a Lima that no longer exists. This communication will try to explain many of the aspects that need to be known in order to better understand the tradition: “The Barbones”, and with this, to revalue the role of a diligent historian and an ingenious writer who was the father of the Peruvian Traditions.